Mobile Learning Media Development On Thermochemical Subjects in High School - Seget Tartiyoso (Syntax Corporation Indonesia, 2022)
This study aims: to (1) Know the feasibility level of mobile learning media that has been developed on thermochemical subjects based on BSNP. (2) To determine the level of student learning success on the use of mobile learning media that has been developed with an average student score greater than the KKM score. The population in this study were students of class XI IPA SMA Negeri 1 Stabat. This research is a type of research One-Group pretest-posttest design. The analysis techniques used are (1) One sample t-test; (2) Two Parties, where the experimental class was given mobile learning media that had been developed. This study uses the method and media development (R&D) with the ADDIE model. The ADDIE model has several stages, namely analysis, design, development, implementation, and evaluation. Where the results of the feasibility analysis of mobile learning media content feasibility aspects are 4.87; the language eligibility is 4.9; presentation feasibility 5 and graphic feasibility 4,6. By using mobile learning media on thermochemical material, an increase in learning outcomes was obtained by 66% with the highest score of 95 and the lowest score of 75 where the postest average score of 86.72 had passed the KKM of 80. Hypothesis testing was carried out to produce results tcount> table, namely 7, 13> 2,0399. It can be concluded that the development of this media can improve student learning outcomes.